2015
DOI: 10.4253/wjge.v7.i4.429
|View full text |Cite
|
Sign up to set email alerts
|

Bowel perforation due to break and distal passage of the safety ring of an adjustable intra-gastric balloon: A potentially life threatening situation

Abstract: A 45-year-old man of Middle Eastern origin, morbid obese, with a body mass index of 39 had an intra-gastric balloon, filled with 500 mL of saline/methylene blue and intended as definite therapy, inserted some 8 wk previously. He was admitted to the emergency department with abdominal cramps. An ultrasound of the abdomen was performed in ER which confirmed the balloon to be in place without any abnormality. He was discharged home on symptomatic medication. Patient remains symptomatic therefore he reported back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These thresholds include a 12-month EWL of 25% in patients with a BMI Z35, as well as a maximum 5% risk of serious adverse events [41,42] . Our 512 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 618 619 620 621 review has suggested promising early results for the ORBERA balloon: 30%-50% EWL upon device removal, with nausea, vomiting, and stomach pain as the most common complications and a serious adverse event rate of approximately 1% [8,9,43]...…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These thresholds include a 12-month EWL of 25% in patients with a BMI Z35, as well as a maximum 5% risk of serious adverse events [41,42] . Our 512 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 618 619 620 621 review has suggested promising early results for the ORBERA balloon: 30%-50% EWL upon device removal, with nausea, vomiting, and stomach pain as the most common complications and a serious adverse event rate of approximately 1% [8,9,43]...…”
Section: Discussionmentioning
confidence: 95%
“…Typical complications include nausea, vomiting, and stomach pain that resolve within 72 hours. More serious adverse events include balloon migration and bowel perforation due to the break and distal passage of a balloon's safety ring, which can be lifethreatening [8,9]. In most studies, percent excess weight loss (%EWL) at the time of device removal ranges from 30-50 [10][11][12].…”
Section: Space-occupying Devicesmentioning
confidence: 99%
“…Of interest, the patients were on continuous proton pump inhibitors and no gastro-toxic drugs intake was noted prior to the perforative complications. As stated by the authors, the Spatz 3 ABS, with its new upgraded design with a soft catheter instead of the rigid catheter and metal chain is supposed to avoid the reported incidents of perforation or requirement for surgery secondary to catheter impaction or dislodgement [2][3][4]. Nevertheless, we believe that the sequential placement of two BIB balloons may prove to be safer on the long term, although not costefficient relative to the placement of a single Spatz balloon with upward adjustment when needed.…”
Section: Casementioning
confidence: 88%
“…The prevalence and increase of obesity in the world are that 2.3 billion adults were overweight and 700 million adults were obese in 2015 [1,2]. In Brazil, according to Brazilian Institute of Geography and Statistics, in the 34 years that have passed, the prevalence of overweight adults increased by almost three times in males (18.5% to 50.1%) and almost twice in women (from 28.7% to 48.0%) [3,4].…”
Section: Introductionmentioning
confidence: 99%